METHODS OF DIGITIZATION IN THE APPLICATION OF MODERN MEDICAL TECHNOLOGIES - Tukhtakhodjayeva F.Sh., Sayfiddin Khoji K.Sh., Murodullayev M.N. (Central Asian Journal of Medicine, 2025)
This article explores the transformative role of digitization in modern medical technologies, focusing on key methods such as Electronic Health Records (EHRs), telemedicine, medical imaging, wearable devices, artificial intelligence (AI), and blockchain. It examines their applications, benefits, and challenges in enhancing healthcare delivery, efficiency, and patient outcomes. Supported by a flowchart illustrating the digitization workflow and a bar chart visualizing adoption trend, the article highlights how digital solutions drive innovation in healthcare while addressing barriers like data security and implementation costs. It underscores the importance of continued investment in digital infrastructure to shape the future of medical practice.